Skilled trade professionals a practical career guide - Collins, Corbin (Practical career guides., 2019)
Skilled Trade Professionals includes interviews with professionals in the field, covers five main areas of this field that have proven to be stable, lucrative, and growing professions. Electrician HVAC Technician Plumber Construction Laborer, Craftsperson, and Manager Automotive Service Technician/Mechanic.